A bibliometric overview of the Journal of Network and Computer Applications between 1997 and 2019. (1st September 2020) - Zurita, Gustavo; Shukla, Amit K.; Pino, José A.; Merigó, José M.; Lobos-Ossandón, Valeria; Muhuri, Pranab K.
Abstract: A bibliometric analysis of the Journal of Network and Computer Applications (JNCA) for the 1997–2019 period is performed. This analysis uncovers the structural and hidden implications of this journal. JNCA is one of the most prestigious journals in the computer science and engineering research community. Clarivate Analytics Web of Science is used to extract the bibliometric data on which the analysis is performed. The study begins with the publication and citation structure. Analysis of the most influential papers is discussed next. Detailed information on leading authors, institutions and countries is also presented. Analysis of the co-citations, bibliographic coupling, and co-occurrence of keywords was performed with the help of VOSviewer as a visualization tool. Alongside visual analysis, temporal and global analyses are also presented for the co-citation analysis and co-occurrence analysis.